IMPORTANCIA DE LOS CONSULTORIOS EN ASESORÍAS TÉCNICAS Y ADMINISTRATIVAS EN LAS INSTITUCIONES DE EDUCACIÓN SUPERIOR - Méndez Becerra, Mónica Valeria
The main objective of this research is to identify the importance and feasibility of business consulting models in higher education. A mixed documentary research is carried out in which other similar models and time line investigations are analyzed. The constructivist theory is also analyzed as a pedagogical model based on learning, using as a strategy laboratories and business practices, which yields a first hypothesis of including these theories as guarantors of an apprehension of knowledge in a real context and as a first approach application of surveys of the perception of the productive sector to microentrepreneurs in the town of Suba in front of these consulting models. The main result was the research in the research and the confidence in a large percentage of the microentrepreneurs when they were advised by students and teachers in the business offices of higher education. Another important result obtained was that microentrepreneurs are willing to pay for these consultancies, which makes this a medium-term model of the sea that is self-sustaining. Finally, it was possible to know the most important areas regarding the perspective of the entrepreneurs, take into account for the taking of consultancies and strengthening the knowledge of them.